2001
DOI: 10.1002/jbm.1246
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylapatite with substituted magnesium, zinc, cadmium, and yttrium. I. Structure and microstructure

Abstract: Hydroxylapatite (HA) was made containing magnesium, zinc, cadmium, and yttrium. Salts of these cations were added to precipitating HA; the precipitates were dried and sintered at 1100 degrees C for 1 h. Lattice parameters from X-ray diffraction spectra showed that these elements were incorporated into the apatite structure at a level of 2% added fraction of calcium in HA and up to 7% for yttrium. The densities of different substituted apatites were close to theoretical for pressed and sintered samples, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(119 citation statements)
references
References 8 publications
1
116
1
1
Order By: Relevance
“…This is clearly not a compensatory response, as males grow faster than females. In addition to other roles, Mg plays an important role in bone formation because it can substitute Ca in bone hydroxyapatite, and in fact, 3% of bone is formed by Mg 3 (PO 4 ) 2 (Doyle 1979, Ergun et al 2002. The reason for a higher Mg content in milk for males might be linked to the role Mg plays in the skeleton because 70% of the body reserves of Mg are in the skeleton (Doyle 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is clearly not a compensatory response, as males grow faster than females. In addition to other roles, Mg plays an important role in bone formation because it can substitute Ca in bone hydroxyapatite, and in fact, 3% of bone is formed by Mg 3 (PO 4 ) 2 (Doyle 1979, Ergun et al 2002. The reason for a higher Mg content in milk for males might be linked to the role Mg plays in the skeleton because 70% of the body reserves of Mg are in the skeleton (Doyle 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for a higher Mg content in milk for males might be linked to the role Mg plays in the skeleton because 70% of the body reserves of Mg are in the skeleton (Doyle 1979). In fact, the substitution of Ca by Mg makes the hydroxyapatite more compact and thus can have mechanical consequences for the skeleton (Ergun et al 2002). Similarly, K seems to play an important role in bone formation which has not been recognized until very recently.…”
Section: Discussionmentioning
confidence: 99%
“…6), 7) Magnesium (Mg) activates osteoblasts and osteoclasts, and not only promotes bone remodeling but also affects the nucleation and crystal growth of HAp. 8), 9) Several studies have demonstrated the varied properties of potassium (K) for the control of biochemical processes and the important role K plays in the apatite mineral nucleation process. 10), 11) As concerns anions, it is well known that fluor-ine (F) in the apatite phase is responsible for higher chemical and thermal stability.…”
Section: )5)mentioning
confidence: 99%
“…3 because of the potential beneficial effects of Mg on the physicochemical properties of the minerals [14,15] and also because the improvement of the bone metabolism [16].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%